1121. Implementation and Evaluation of a Virtual Microbiology Laboratory for Pharmacy Students. (31st December 2020) - Gruenberg, Katherine; Trinh, Trang D; Joyce, Elizabeth; MacDougall, Conan
Abstract: Background: Health professions students learn microbiology concepts during in-person laboratories (labs). While highly rated by students, labs are extremely resource- and time-intensive. A virtual lab may minimize resource use while maintaining educational value. We report on the implementation and evaluation of a virtual lab designed to teach clinical microbiology to pharmacy students during an infectious diseases course. Methods: We created a video in our clinical microbiology lab to depict the steps involved in processing and analyzing a patient sample. We also designed 2 web-based, interactive modules for students to practice lab techniques, such as virtually streaking an agar plate. Students viewed the video and completed the modules prior to attending a 2-hour in-person, case-based, small group discussion on higher-order clinical microbiology concepts. All students were invited to complete a post-session evaluation that assessed achievement of session objectives. Results: Sixty-nine students (65%) completed the survey. Students highly rated the video, modules, and in-class cases (Table 1). Fewer students felt confident explaining the clinical microbiology process, compared to selecting antibiotics, interpreting cultures, explaining Gram stains, and interpreting an antibiogram (Table 2). Student comments highlighted the value of the video, modules, and instructor facilitation during the in-class session. Students also suggested improvements with the module user interface and reinforcement of certain topics (e.g. clinical breakpoints) during the in-class session. Table 1: Student Ratings of the Quality of Instructional Materials Table 2: Student Self-Reported Agreement with Achievement of Session Objectives Conclusion: We demonstrated successful implementation a virtual microbiology lab within a pharmacy course. Overall student ratings of materials were favorable. We plan to refine and re-offer the virtual micro lab next year and measure its association with student performance. To facilitate the adaptation of this virtual lab by other schools, our teaching materials are available for use via https://vimeo.com/390087512 (video) and http://tiny.ucsf.edu/atlas (modules). Disclosures: All Authors : No reported disclosures